Correction: Near-infrared emitting single squaraine dye aggregates with large Stokes shifts. Issue 42 (23rd October 2017) - Paternò, G. M.; Moretti, L.; Barker, A. J.; D'Andrea, C.; Luzio, A.; Barbero, N.; Galliano, S.; Barolo, C.; Lanzani, G.; Scotognella, F.
Abstract : Correction for 'Near-infrared emitting single squaraine dye aggregates with large Stokes shifts' by G. M. Paternò et al., J. Mater. Chem. C, 2017, 5, 7732–7738.